2012
DOI: 10.1523/jneurosci.4406-10.2012
|View full text |Cite
|
Sign up to set email alerts
|

Change in Choice-Related Response Modulation in Area MT during Learning of a Depth-Discrimination Task is Consistent with Task Learning

Abstract: What are the neural mechanisms underlying improvement in perceptual performance due to learning? A recent study using motiondirection discrimination suggested that perceptual learning is due to improvements in the "readout" of sensory signals in sensory-motor cortex and not to improvements in neural sensitivity of the sensory cortex. To test the generality of this hypothesis, we examined this in a similar but different task. We recorded from isolated neurons in the middle temporal (MT) area while monkeys were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…One of the biggest debates in the field of perceptual learning concerns the locus where learning takes place. Usually, perceptual learning is thought to occur either in the early sensory areas (Adab & Vogels, 2011;Crist et al, 2001;Karni & Sagi, 1991;Raiguel et al, 2006;Schoups et al, 2001;Yang & Maunsell, 2004) or decision making stages (Dosher & Lu, 1998, 1999Law & Gold, 2008;Petrov et al, 2005;Uka et al, 2012). Perceptual learning is usually very specific for the stimuli trained with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest debates in the field of perceptual learning concerns the locus where learning takes place. Usually, perceptual learning is thought to occur either in the early sensory areas (Adab & Vogels, 2011;Crist et al, 2001;Karni & Sagi, 1991;Raiguel et al, 2006;Schoups et al, 2001;Yang & Maunsell, 2004) or decision making stages (Dosher & Lu, 1998, 1999Law & Gold, 2008;Petrov et al, 2005;Uka et al, 2012). Perceptual learning is usually very specific for the stimuli trained with.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Vision, 17(6):6, 1-11, doi:10.1167/17.6.6. Dosher, & Lu, 2005;Uka, Sasaki, & Kumano, 2012). Motor processing, related to the motor response, is thought to play no role for and in the learning process, simply because the stimulus-response mapping is arbitrary.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in dorsal stream areas, middle temporal and medial superior temporal, showed no perceptual learning effects on neural tuning or response strength during direction (Law & Gold, 2008), heading (Gu et al, 2011), or depth discrimination tasks (Uka, Sasaki, & Kumano, 2012). In these areas, the correlation between behavioral choices and neural responses increased during early task learning for depth discrimination (Uka et al, 2012) and during direction discrimination learning (Law & Gold, 2008), which may suggest that the learning to discriminate involves a reweighting of the stable visual cortical signals that are used to form the perceptual decision (Law & Gold, 2009). This idea is supported by evidence of perceptual learning-induced changes in decision-related responses of lateral intraparietal neurons to the choice targets in the motion direction task (Law & Gold, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Initial studies showed changes in the tuning of macaque V1 and V4 neurons after extensive training in a fine orientation discrimination task (Raiguel, Vogels, Mysore, & Orban, 2006;Yang & Maunsell, 2004;Schoups, Vogels, Qian, & Orban, 2001) with smaller and less consistent effects across studies in V1 (Ghose, Yang, & Maunsell, 2002;Schoups et al, 2001). However, studies in dorsal stream areas, middle temporal and medial superior temporal, showed no perceptual learning effects on neural tuning or response strength during direction (Law & Gold, 2008), heading (Gu et al, 2011), or depth discrimination tasks (Uka, Sasaki, & Kumano, 2012). In these areas, the correlation between behavioral choices and neural responses increased during early task learning for depth discrimination (Uka et al, 2012) and during direction discrimination learning (Law & Gold, 2008), which may suggest that the learning to discriminate involves a reweighting of the stable visual cortical signals that are used to form the perceptual decision (Law & Gold, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…read-out weights—within a day’s session (e.g. Cohen and Newsome, 2009; Sasaki and Uka, 2009), these strategies must first be learned via a mechanism akin to reinforcement learning over the course of weeks or months of training (Law and Gold, 2008, 2009; Uka et al, 2012). We saw no evidence of the gradual improvements in performance that would accompany such learning either within or across sessions (Figure S1), even though we monitored behavioral performance of both animals from the first cooling day.…”
Section: Resultsmentioning
confidence: 99%